2019
DOI: 10.1039/c8tc05451g
|View full text |Cite
|
Sign up to set email alerts
|

Ferroelectric transitions in silver niobate ceramics

Abstract: Silver niobate (AgNbO3)-based dielectric materials show great application potential in pulse power energy storage systems due to their high energy storage density.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
29
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 41 publications
(35 citation statements)
references
References 43 publications
4
29
0
1
Order By: Relevance
“…Next we consider the nature of the proposed P2 1 ma to Pcam transition. It is not possible to distinguish the Pcam and P2 1 am structures from the appearance of the PND profiles, since these two space groups allow the same reflections, although Yashima 44 and Tian 45 have shown by using electron diffraction that the latter space group is appropriate at room temperature. Niranjan et al 46 reported that the P2 1 am model provided a superior fit to medium resolution PND data compared with the nonpolar Pbcm (alternate setting of Pcam).…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
“…Next we consider the nature of the proposed P2 1 ma to Pcam transition. It is not possible to distinguish the Pcam and P2 1 am structures from the appearance of the PND profiles, since these two space groups allow the same reflections, although Yashima 44 and Tian 45 have shown by using electron diffraction that the latter space group is appropriate at room temperature. Niranjan et al 46 reported that the P2 1 am model provided a superior fit to medium resolution PND data compared with the nonpolar Pbcm (alternate setting of Pcam).…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
“…2b. 13,16 The discovery of "double" polarization hysteresis under strong electric elds indicated that AgNbO 3 could potentially replace Pb-based antiferroelectrics in energy storage applications. Based on chemical composition adjustments, the eldinduced phase transitions and the associated physical properties can be optimized.…”
Section: Introductionmentioning
confidence: 99%
“…1−5 The discharged energy density of a capacitor (U c ) is expressed as U c = ∫ EdD, where D is the electric displacement and E is the dielectric breakdown strength. 6 D is described as D = ε r E, which means large ε r (dielectric constant) tends to increase D under the applied electric field. However, there are still critical challenges that maximize both dielectric breakdown strength (E b ) and dielectric constant (ε r ) for high-performance dielectric materials.…”
Section: ■ Introductionmentioning
confidence: 99%